(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
CoViD-19 pandemic is being managed with social distancing measures based on the precautionary principle. Thereby civil liberties have been severely limited and many questions have arisen on how to balance protection of public health and individual freedoms. In this framework the precautionary principle should be thought as a public policies’ compass for the future, by protecting the relation between science and society, especially through institutional communication.